Integration of Pretreatment With Simultaneous Counter-Current Extraction of Energy Sorghum for High-Titer Mixed Sugar Production - Williams, Daniel L.; Ong, Rebecca G.; Mullet, John E.; Hodge, David B. (Frontiers in Energy Research, 2019)
Sorghum (Sorghum bicolor L. Moench) offers substantial potential as a feedstock for the production of sugar-derived biofuels and biochemical products from cell wall polysaccharides (i. e., cellulose and hemicelluloses) and water-extractable sugars (i.e., glucose, fructose, sucrose, and starch). A number of preprocessing schemes can be envisioned that involve processes such as sugar extraction, pretreatment, and densification that could be employed in decentralized, regional-scale biomass processing depots. In this work, an energy sorghum exhibiting a combination of high biomass productivity and high sugar accumulation was evaluated for its potential for integration into several potential biomass preprocessing schemes. This included counter-current extraction of water-soluble sugars followed by mild NaOH or liquid hot water pretreatment of the extracted bagasse. A novel processing scheme was investigated that could integrate with current diffuser-type extraction systems for sugar extraction. In this approach, mild NaOH pretreatment (i.e., <90°C) was performed as a counter-current extraction to yield both an extracted, pretreated bagasse and a high-concentration mixed sugar stream. Following hydrolysis of the bagasse, the combined hydrolysates derived from cellulosic sugars and extractable sugars were demonstrated to be fermentable to high ethanol titers (>8%) at high metabolic yields without detoxification using a Saccharomyces cerevisiae strain metabolically engineered and evolved to ferment xylose.